Pengaruh Model Pembelajaran Kooperatif Tipe Make A Match Terhadap Hasil Belajar Pada Menulis Teks Anekdot Peserta Didik Kelas X SMA Negeri 5 Kerinci. - Ria Agustina; Suci Maiza; Riska Melati (Journal on Education, 2023)
This research is based on anecdote text writing ability. Most of the students had difficulties when they write an anecdote text. Most of them were unmotivated to write immediately. Beside that, some students’ score in writing were also low. It can be seen from their score which were below the KKM. Even though the teaching techniques chosen and practiced by the teacher in teaching writing greatly impact the learning achievement of the students, some of the them were not able to present the writing material in an interesting, inspiring and creative way. This learning model made it hard for the students to write the anecdote text. The theories used as the references in this research were Isjoni’s opinion about cooperative learning model and Kebol’s about the anecdote text. This research was an experimental research. The research population was grade X students which consist of 2 classes with the total number of students was 40 students. The sample of this research was taken by doing random sampling. X MIPA 1 class was chosen as the experimental class. In other hand X MIPA 2 was chosen as the control class. Each of this class was consisted of 20 students. The result of this research showed that the cooperative learning model of the Make A Match type is appropriate for learning to write anecdotal texts for class X students of SMA Negeri 5 Kerinci because this model can influence writing skills. It was proven by average score of students in the experimental class, 87.60, which is higher than the control class, which is 76.75.Based on the research result we can conclude that Make A match type of cooperative learning model has significant effect on students’ ability in writing anecdote text at grade X SMAN 5 Kerinci